An Analysis Of Factors Affecting Users' Decisions Of Online Ojek Services In Bengkulu City - Saputra, Debi Tri Saputra; Soleh, Ahmad; Irwanto, Tito (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
The people of Bengkulu now can use online ojek services and they can be accessed by the public as an alternative mode of transportation for their activities. In increasing decision to use online ojek services, this will be influenced by the service marketing mix. The aim of this research is to determine the factors affecting users’ decision of online ojek services in Bengkulu city. The sample in this study was 145 people from Bengkulu city who used online ojek. The sampling technique is accidental sampling. Data were collected using a questionnaire and the analysis methods used were multiple linear regression, determination tests and hypothesis tests. The research results show the regression equation Y = 4.179 + 0.222 (X1) + 0.055 (X2) + 0.217 (X3) + 0.351 (X4) + 0.277(X5) + 0.292 (X6) - 0.094 (X7). The results of partial hypothesis testing research show that the variables Product (X1) Promotion (X3), Distribution (X4), People (X5), Process (X6) have a significant influence on users’ decision of online ojek services (Y) while the variable Price (X2) and Physical Environment (X7) has an insignificant influence on users’ decision of online ojek services (Y). Simultaneous testing shows a significance value of 0.000, less than 0.05, indicating that together Product (X1), Price (X2), Promotion (X3), Distribution (X4), People (X5), Process (X6) and Physical Environment (X7) has a significant influence on users’ decision of online ojek services (Y).